A study on the compressive strength of three-dimensional direct printing aligner material for specific designing of clear aligners - Byeong Gu Bae; Young Ho Kim; Gun Ho Lee; Jiho Lee; Jinhong Min; Hoon Kim; Jeong Won Shin; Hwa Sung Chae (Scientific Reports)
Abstract Background The demand for orthodontic treatment using clear aligners has been gradually increasing because of their superior esthetics compared with conventional fixed orthodontic therapy. This study aimed to evaluate and compare the compressive strength of three-dimensional direct printing aligners (3DPA) with that of conventional thermo-forming aligners (TFA) to determine their clinical applicability. In the experimental group, the 3DPA material TC-85 (TC-85 full) was used to create angular protrusions called rectangular pressure areas (RPA). A protrusion akin to the power ridge typically employed in conventional TFAs was created using glycol-modified polyethylene terephthalate (PETG; Control 1). RPA was created using the same TC-85 without filling the protrusions (TC-85 blank; Control 2). Compression cycle tests were conducted on an LTM 3 h electrodynamic testing machine (Zwick Roell, Germany), with 500 cycles and compression depths of 100, 300, 500, and 700 µm. Twenty specimens were tested for PETG, 17 for the TC-85 blank, and 19 for the TC-85 full. Results Changes in the compressive force were assessed based on the material and thickness. The results indicated significantly higher and broader ranges of compressive strength for specimens fabricated with the 3DPA material TC-85 compared with those fabricated using PETG. Among the TC-85 specimens, TC-85 full demonstrated the highest statistically significant compressive strength . Conclusions 3DPA technology enables precise modifications in the shape and inner thickness at specific dental sites, including the creation of ridges in targeted areas, of aligners. These alterations enhance the biomechanical capability of aligners to exert selective forces necessary for desired tooth movement while reducing the number of attachments, thereby demonstrating the clinical potential of 3D-printed aligners in orthodontic treatment.